The Influence of Business Competence, Access to Capital, and Marketing Strategy Creativity on Student Business Performance in the Entrepreneurial Student Development Program - Wibowo, Yohanes Gunawan; Izzuddin, Ahmad (Ilomata International Journal of Management, 2025)
This study investigates the impact of business competence and access to capital on student business performance, with marketing strategy creativity serving as a mediating variable within the Entrepreneurial Student Development Program (P2MW). Using a quantitative associative approach, data were collected from 120 students representing 57 universities across Indonesia at the 14th KMI Expo, and analyzed through Structural Equation Modeling (SEM) with WARP PLS 07. The findings reveal that business competence and access to capital significantly influence both marketing strategy creativity and business performance. Furthermore, marketing strategy creativity plays a crucial mediating role, amplifying the effects of both independent variables, with business competence showing the strongest influence. These results underscore the importance of integrating entrepreneurial skills and financial access with innovative marketing strategies to enhance the performance of student-led ventures. The study’s cross-sectional design and lack of demographic analysis pose limitations. Future research should employ longitudinal methods and explore demographic variations to deepen understanding and guide policy for more effective entrepreneurship education.